2000
DOI: 10.1046/j.1365-2141.2000.01963.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6, tumour necrosis factor α, interleukin 1β and interleukin 1 receptor antagonist promoter or coding gene polymorphisms in multiple myeloma

Abstract: Summary. Proinflammatory cytokines such as interleukin 6 (IL-6), tumour necrosis factor a (TNF-a ) and IL-1b are considered to be involved in the pathogenesis of multiple myeloma (MM). In the present study, we examined a G/C polymorphism at position 2174 in the promoter region of IL-6, a biallelic polymorphism at position 2308 in the promoter region of TNF-a , the TaqI restriction fragment length polymorphism in exon 5 of IL-1b and a variable number of identical tandem repeat polymorphisms in intron 2 of IL-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
60
3
6

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 53 publications
8
60
3
6
Order By: Relevance
“…Poorly defined control groups, possibly due to population stratification resulting from ethnic admixture within the study population, may result in poor matching with a patient group, resulting in the identification of spurious differences in allele frequencies and leading to an initial impression of an association between a gene variant and a given condition. Examples may be the study by Cvetkovic et al 31 in which the carriage of the TNF À308 G allele was found to be higher in patients compared to the control group used, while other Swedish studies, 54,123,124 including two previous studies from the same group 125,126 have reported allele frequencies in healthy controls that are very similar to the patient group in this study. Similarly, Yen et al 30 included a healthy control group that showed very striking differences in allele frequencies to the patient population, but against a background of some confusion as to the true allele frequencies in the Taiwanese population.…”
Section: Disease Associations-conclusionsupporting
confidence: 43%
“…Poorly defined control groups, possibly due to population stratification resulting from ethnic admixture within the study population, may result in poor matching with a patient group, resulting in the identification of spurious differences in allele frequencies and leading to an initial impression of an association between a gene variant and a given condition. Examples may be the study by Cvetkovic et al 31 in which the carriage of the TNF À308 G allele was found to be higher in patients compared to the control group used, while other Swedish studies, 54,123,124 including two previous studies from the same group 125,126 have reported allele frequencies in healthy controls that are very similar to the patient group in this study. Similarly, Yen et al 30 included a healthy control group that showed very striking differences in allele frequencies to the patient population, but against a background of some confusion as to the true allele frequencies in the Taiwanese population.…”
Section: Disease Associations-conclusionsupporting
confidence: 43%
“…Our results are similar to the results reported by Zheng et al (7) and Mazur et al (13). The G allele frequency was higher in the Brazilian population (75% among patients and 77% among controls) than in the European population (7,13). This observation could be explained by the different ethnic background of the Brazilian population.…”
supporting
confidence: 80%
“…The presence of lysine (allele C) at the guanine site (allele G) is associated with low levels of plasma IL-6 in healthy subjects. The CC genotype is considered to be a low producer and GG a high producer of IL-6 (4,7,8). However, Endler et al (6) did not find this association and Brull et al (9) found the opposite, i.e., patients with the CC allele had higher plasma IL-6 levels.…”
mentioning
confidence: 69%
“…Despite prior in vitro and in vivo evidence and the hypothesis that high-functioning variation in genes from both T H 1 and T H 2 pathways could predispose individuals to increased MM risk, the results from our study and from others [16][17][18][19] provide evidence that the independent effects of genetic variation in IL1B, IL6, IL10, LTA, TNF and CTLA4 do not strongly influence susceptibility to MM. IL-6 is considered the primary mediator contributing to the autocrine 51 and paracrine monoclonal expansion [52][53][54][55][56] and survival 57,58 of MM tumor cells both in the bone marrow microenvironment and in vitro.…”
Section: Discussioncontrasting
confidence: 43%
“…Expression levels of cytokines and adhesion molecules can be regulated, in part, by functional genetic variation. Findings from previously published gene association studies suggested that common variants of IL6, IL1B or haplotypes of IL10 do not substantially influence susceptibility to MM, [16][17][18][19] while correlations of MM with variants in cytotoxic T-lymphocyte antigen-4 (CTLA4), lymphotoxin-a (LTA), TNF and haplotypes that account for variation in the LTA*TNF complex (6p21) remain less clear. 16,[20][21][22] In this investigation, we examined whether common genetic variants from proinflammatory and antiinflammatory cytokine, interferon, chemotactic and cell-adhesion molecule, growth factor, signal transduction and cell cycle and immune regulation pathways, in addition to IL6, IL10, CTLA4, TNF and LTA, influence risk of MM.…”
mentioning
confidence: 98%